1992
DOI: 10.1063/1.462284
|View full text |Cite
|
Sign up to set email alerts
|

High resolution x-ray photoelectron spectroscopy study of Cr(CO)6 in the gas phase

Abstract: The gas phase high resolution x-ray photoelectron spectra of the Cr(CO)6 metal complex are presented. The valence electron spectrum and the core level spectra including the associated satellite structures from the Cr, C, and O atoms are discussed. Comparison to free CO and to CO adsorbed on metal surfaces are made. An assignment of the valence levels is achieved using an intensity model. The anomalous dispersion of the narrow band in CO adsorbed on Cu seems to be related to the localization properties of the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
26
0

Year Published

1992
1992
2009
2009

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 48 publications
3
26
0
Order By: Relevance
“…Other studies identified only three or four peaks in this region. 22,23 The SAC-CI spectrum in Figs. 1-3 indicated four or five peaks in this region with this FWHM.…”
Section: A Ionization Spectramentioning
confidence: 99%
See 2 more Smart Citations
“…Other studies identified only three or four peaks in this region. 22,23 The SAC-CI spectrum in Figs. 1-3 indicated four or five peaks in this region with this FWHM.…”
Section: A Ionization Spectramentioning
confidence: 99%
“…They have been widely studied as a prototype for understanding the chemical bonds of organometallic compounds 18,19 or a model for adsorption of carbon monoxide on metal surfaces. 20 On the ionizations in the valence region, He I and He II PES, 21 x-ray PES ͑XPES͒, 22 synchrotron radiation PES ͑SRPES͒, 23,24 and PIES ͑Ref. 25͒ have been reported for Cr͑CO͒ 6 , Mo͑CO͒ 6 , and W͑CO͒ 6 .…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…A larger energy spread in the calculated spectrum is expected and typical for the INDO method and can be explained by the partial neglect of electron repulsion effects in the INDO method. Therefore, the calculated spectra have been normalized by an energy-spread factor of 0.63, obtained from a comparison between an experimental XPS spectrum of the Cr(C0)6 molecule [32] and a theoretical DOS calculated with the ZINDO program.…”
Section: Dos For Clusters With Bulk Crystalmentioning
confidence: 99%
“…If the temperature dependence of the reaction step is described by Eqn [13], from the slope of the fitted line between 310 and 240°C in . The physical meaning of Q c energy is different from that of DH c , i.e.…”
mentioning
confidence: 99%